(untitled) (Innovaciones Educativas, 2023)
Plagiarism is a problem associated with various causes and motivations that have a significant impact on students with a certain vulnerability to this practice. This essay presents an alternative for its approach from a divergent view, which can be incorporated by educational institutions at the curricular level and teachers can use it in their daily work. This approach is based on the universe of free culture, meaningful learning, socio-constructivism, and the implementation of a motivational system in which the student understands and reflects on academic production and is detached from the punitive discourse and the sanctioning perspective. To this end, the objective was to motivate students in the process of knowledge construction, with a clear vocation towards solidarity contribution through their academic productions. The main conclusion of the paper is the recognition of plagiarism as a complex problem that requires self-criticism and responsibility on the part of higher educational institutions, in order to solve the shortcomings and weaknesses in literacy that students carry with them from lower educational levels. In addition, to stimulate the threshold of motivation in the learner, through a discursive change that from the pedagogical mediation and the use of free culture and open access, enriches the academic production and dissemination, where the only aspect of control is mediated by the respect for the integrity of the products made available and the corresponding authorship of those who produce them.